2008
DOI: 10.1111/j.1399-3046.2008.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Can pediatric steroid‐free renal transplantation improve growth and metabolic complications?

Abstract: We analyzed the effects of a steroid avoidance protocol in pediatric renal transplant recipients on calculated CrCl (Schwartz), CMV infection, cholesterol, height Z scores, weight Z scores, and BMI Z scores in a case control trial with contemporaneous controls. From 1999 to 2004, 19 pediatric patients (age 1-20 yr) received transplants without steroids using immunosuppression with tacrolimus, mycophenolate mofetil, and daclizumab. Control patients (n = 30) were matched for length of follow-up (minimum one yr),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Other single-center studies confirmed these findings (26). However, the studies were not prospective and included few African-American recipients, a traditionally high risk group.…”
Section: Introductionsupporting
confidence: 60%
“…Other single-center studies confirmed these findings (26). However, the studies were not prospective and included few African-American recipients, a traditionally high risk group.…”
Section: Introductionsupporting
confidence: 60%
“…These tacrolimus exposure levels were established in a previous study (10 (27). (5,8,16,29) and 0 to 21% with early steroid withdrawal regimens (9,30,31 …”
Section: This Large Randomized Open-label Comparative Multicenter mentioning
confidence: 99%
“…Several trials of complete steroid avoidance (5)(6)(7)(8)(9) or early steroid withdrawal (10)(11)(12) in pediatric patients have been published with encouraging results, with graft survival and incidence of acute rejection similar to steroidbased protocols. These studies, however, have been mostly limited to single center experiences.…”
Section: Introductionmentioning
confidence: 99%